2013
DOI: 10.4318/tjg.2013.0654
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different mechanisms on the development of post-ERCP pancreatitis in an ERCP model in rats

Abstract: Girifl ve (s›ras›yla, p=0.551, p=0.031, p=0.0001, p=0.0001, p=0.0001, p=0.0001, p=0.683 excess (p=0.551, p=0.031, p=0.0001, p=0.0001, p=0.0001, p=0.0001, p=0.683, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The leakage might be exacerbated by increased intrapancreatic duct pressure with hyper-secretion of pancreatic juice due to PAR-2 activation ( 21 ), especially under conditions of a disturbed pancreatic juice flow caused by ERCP-induced papillary injury due to direct endoscopic trauma with hemorrhaging or edema ( 6 , 7 ). This hypothesis is consistent with that of a previous report stating that increased intrapancreatic duct pressure is responsible for pancreatic parenchymal damage ( 22 ).…”
Section: Discussionsupporting
confidence: 94%
“…The leakage might be exacerbated by increased intrapancreatic duct pressure with hyper-secretion of pancreatic juice due to PAR-2 activation ( 21 ), especially under conditions of a disturbed pancreatic juice flow caused by ERCP-induced papillary injury due to direct endoscopic trauma with hemorrhaging or edema ( 6 , 7 ). This hypothesis is consistent with that of a previous report stating that increased intrapancreatic duct pressure is responsible for pancreatic parenchymal damage ( 22 ).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, other studies show that intraductal regulation of pH (Noble et al, 2008) and the mechanical damage caused by direct papillary trauma (Bozkurt et al, 2013) were found to affect the onset of AP, and might be an important factor in PEP. What is more, some studies show that no correlation was detected with increasing pressure or with the use of contrast agent (Haciahmetoglu et al, 2008).…”
Section: Endoscopymentioning
confidence: 99%
“…However, for mechanical, chemical, hydrostatic, enzymatic, infectious, allergic, and thermal mechanisms that are suspected to trigger PEP, evidence demonstrates that one or more of them are responsible for PEP or influence its severity. 4 Several pharmacologic agents have been tried to avoid or alleviate PEP, such as anti-inflammatories (indomethacin and diclofenac), 5 antioxidants (allopurinol and N -acetylcysteine [NAC]), 6 , 7 antibiotics, 8 and epinephrine. 9 Rectal non-steroidal anti-inflammatory drugs are the cornerstone of PEP prevention according to the European Society of Gastrointestinal Endoscopy guidelines.…”
Section: Introductionmentioning
confidence: 99%